Path Analysis on the Influence of Educational Level, Stages of Cancer, Social Support, and Coping Strategy toward the Quality of Life of Breast Cancer Patients in Dr. Moewardi Hospital, Surakarta - Sri Nuryati; Ambar Mudigdo; Bhisma Murti (Masters Program in Public Health, 2017)
Background: Breast cancer develops into main health problem for women globally. Patients of breast cancer will endure transformation both physically as well as psychologically, it will give impact to the quality of life. The study aimed to analyze the influence of educational level, stages of cancer, social support, and coping strategy toward the quality of life of breast cancer patients.Subjects and Method: The study employed mixed method with quantitative and qualitative approach. The study was conducted in Dr. Moewardi Hospital, Surakarta in August – October 2017. There were a total of 150 study subjects selected with stratified random sampling. Purposive sampling was used for qualitative study with 3 informants. The dependent variable was quality of life. The independent variables were educational level, stages of cancer, social support and coping strategy. Quantitative data collection was conducted by using questionnaires. Social support variable was measured by using Multidimensional scale of perceived social support (MSPSS) questionnaires, coping strategy variable was measured by brief COPE questionnaires and life quality variable was measured by WHOQOL BREF questionnaires. Data qualitative collection was by means in depth interview. Quantitative data was analyzed by using path analysis, qualitative data was analyzed by using interactive model Miles and Huberman.Result: Quality of life was influenced by educational level (b= 8.69, SE= 1.84, p<0.001), stages of cancer (b= -6.41, SE= 2.94, p= 0.029), social support (b= 1.03, SE= 0.34, p= 0.003), coping strategy (b= 2.07, SE= 0.43, p<0.001). Coping strategy was influenced by educational level (b= 0.97, SE= 0.34, p= 0.004) and social support (b= 0.37, SE= 0.06, p<0.001).Conclusion: Quality of life of breast cancer patients is influenced by educational level, stages of cancer, social support, and coping strategy. Coping strategy was influenced by educational level and social support. Key words: social support, coping strategy, quality of life, path analysisCorrespondence: Sri Nuryati. Masters Program in Public Health, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: sri.nuryati1985@gmail.com. Mobile: +6282138283802.Journal of Epidemiology and Public Health (2017), 2(3): 225-235https://doi.org/10.26911/jepublichealth.2017.02.03.04